Encapsulation of Olive Pomace Extract in Rocket Seed Gum and Chia Seed Gum Nanoparticles: Characterization, Antioxidant Activity and Oxidative Stability - Akcicek, Alican; Bozkurt, Fatih; Akgul, Cansu; Karasu, Salih (MDPI, 2021)
The aim of this study was to determine the potential use of rocket seed and chia seed gum as wall materials, to encapsulate and to prevent degradation of olive pomace extract (OPE) in polymeric nanoparticles, and to characterize olive pomace extract-loaded rocket seed gum nanoparticles (RSGNPs) and chia seed gum nanoparticles (CSGNPs). The phenolic profile of olive pomace extract and physicochemical properties of olive pomace, rocket seed gum (RSG), and chia seed gum (CSG) were determined. The characterization of the nanoparticles was performed using particle size and zeta potential measurement, differential scanning calorimeter (DSC), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), encapsulation efficiency (EE%), in vitro release, and antioxidant activity analyses. Nanoparticles were used to form oil in water Pickering emulsions and were evaluated by oxitest. The RSGNPs and CSGNPs showed spherical shape in irregular form, had an average size 318 +/- 3.11 nm and 490 +/- 8.67 nm, and zeta potential values of -22.6 +/- 1.23 and -29.9 +/- 2.57, 25 respectively. The encapsulation efficiency of the RSGNPs and CSGNPs were found to be 67.01 +/- 4.29% and 82.86 +/- 4.13%, respectively. The OPE-RSGNP and OPE-CSGNP presented peaks at the 1248 cm(-1) and 1350 cm(-1) which represented that C-O groups and deformation of OH, respectively, shifted compared to the OPE (1252.53 cm(-1) and 1394.69 cm(-1)). The shift in wave numbers showed interactions of a phenolic compound of OPE within the RSG and CSG, respectively. In vitro release study showed that the encapsulation of OPE in RSGNPs and CSGNPs led to a delay of the OPE released in physiological pH. The total phenolic content and antioxidant capacity of RSGNPs and CSGNPs increased when the OPE-loaded RSGNPs and CSGNPs were formed. The encapsulation of OPE in RSGNPs and CSGNPs and the IP values of the oil in water Pickering emulsions containing OPE-RSGNPs and OPE-CSGNPs were higher than OPE, proving that OPE-loaded RSGNPs and CSGNPs significantly increased oxidative stability of Pickering emulsions. These results suggest that the RSG and CSG could have the potential to be utilized as wall materials for nanoencapsulation and prevent degradation of cold-pressed olive pomace phenolic extract.
Keywords: rocket seed gum; chia seed gum; olive pomace; encapsulation; nanoparticle; SALVIA-HISPANICA L.; INTRINSIC-VISCOSITY; PHENOLIC-COMPOUNDS; DRUG-DELIVERY; NANOENCAPSULATION; OIL; OPTIMIZATION; FABRICATION; COMPONENTS; PARTICLES; Food Science & Technology